Practical Synthesis of Ethynyl(phenyl)-λ3-Iodane Using Calcium Carbide as an Ethynyl Group Source - Hashishin, Takahiro; Osawa, Taisei; Miyamoto, Kazunori; Uchiyama, Masanobu (Frontiers in Chemistry, 2020)
Stannylation of calcium carbide followed by Sn–hypervalent iodine(III) exchange reaction cleanly afforded the electrophilic ethynylating agent ethynyl(phenyl)-λ3-iodane in high yield. This two-step method uses very inexpensive materials and is readily operable without any special precautions.